2018
DOI: 10.3168/jds.2017-13151
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on the effect of incomplete milking during early lactation on ketonemia and body condition loss in Holstein dairy cows

Abstract: Limiting milk production for a short period of time in early lactation could be a relevant strategy to prevent hyperketonemia (HYK). From December 2013 to March 2015, 838 multiparous Holstein cows from 13 herds were enrolled in a randomized controlled trial evaluating the effect of incomplete milking in early lactation on ketonemia and its effect on body condition score (BCS) loss. Cows were randomly assigned 4 wk before expected calving date to 1 of 2 treatment groups, (1) a conventional milking protocol (CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…Finally, Roberts et al (2012) found that odds of culling within the first 60 DIM were increased by 1.8 in cows presenting hyperketonemia (BHB blood concentration ≥1.2 mmol/L) during the first WIM. As the incomplete milking was found to reduce odds of hyperketonemia (Carbonneau et al, 2012;Morin et al, 2018), we would have expected to observe a preventive effect of the incomplete milking on culling; however, this was not the case in our study. Many internal (e.g., parity, health status) and external (e.g., need for producing more milk, milk/price) factors will affect the producer's decision whether to cull a cow (Bell et al, 2010).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Finally, Roberts et al (2012) found that odds of culling within the first 60 DIM were increased by 1.8 in cows presenting hyperketonemia (BHB blood concentration ≥1.2 mmol/L) during the first WIM. As the incomplete milking was found to reduce odds of hyperketonemia (Carbonneau et al, 2012;Morin et al, 2018), we would have expected to observe a preventive effect of the incomplete milking on culling; however, this was not the case in our study. Many internal (e.g., parity, health status) and external (e.g., need for producing more milk, milk/price) factors will affect the producer's decision whether to cull a cow (Bell et al, 2010).…”
Section: Discussionmentioning
confidence: 54%
“…The original study was designed to investigate the effect of an incomplete milking protocol on ketonemia, odds of hyperketonemia, reproductive performances, odds of infectious diseases (e.g., mastitis, metritis), culling hazard and, finally, milk production and composition (Krug et al, 2017;Morin et al, 2018). Among all the outcomes studied, the outcome requiring the largest sample size was odds of hyperketonemia, which required the recruitment of 400 cows per treatment group (Morin et al, 2018). The sample size for the RCT described in our study was, therefore, determined for answering this latter research objective.…”
Section: Sample Size Calculationsmentioning
confidence: 99%
See 3 more Smart Citations